How Do Teachers From Alternative Pathways Contribute to the Teaching Workforce in Urban Areas? Evidence From Kansas City - Yang An; Cory Koedel (SAGE Publishing, 2021)
We examine how teachers from two alternative preparation programs-Teach for America (TFA) and Kansas City Teacher Residency (KCTR)-contribute to the teacher labor market in and around Kansas City, Missouri. TFA and KCTR teachers are more likely than other teachers to work in charter schools and, more broadly, in schools with more low-income, low-performing, and underrepresented minority (Black and Hispanic) students. Teachers from both programs are more racially/ethnically diverse than the larger local-area teaching workforce, but only KCTR teachers are more diverse than other teachers in the same districts where they work. We estimate value added to achievement for teachers in both programs compared with nonprogram teachers, with the caveat that our KCTR sample for this analysis is small. In math, we find large positive impacts of TFA and KCTR teachers on test score growth; in English language arts also, we estimate positive impacts, but they are smaller.